Leaders and followers in hot IPO markets - Banerjee, Shantanu; Güçbilmez, Ufuk; Pawlina, Grzegorz (Journal of Corporate Finance, 2016)
We model the dynamics of going public within an IPO wave. The model predicts that firms with better growth opportunities can find it optimal to go public early and accept underpricing of their issues to signal quality. Data supports this prediction as, on average, early movers underprice their issues significantly more and we show that leaders (early movers with high underpricing) obtain much higher valuations when going public than other IPO firms. Furthermore, after going public, leaders invest significantly more, their sales grow faster, and their profitability remains higher compared to other IPO firms.